KLASIFIKASI PRIORITAS KETERTARIKAN PERILAKU PENGUNJUNG PAMERAN TERHADAP KARYA SENI RUPA KONTEMPORER - Dessy Rachma Waryanti (INVENSI, 2016)
Many elements are presented to visitors during an exhibition of contemporary art. These elements include the overaching concept of the exhibit (Ko), issues raised in the exhibition (Is), the name of the artist whose popularity attracts patrons (Na), and visual forms of the art itself (Vi). Using these four elements I compiled questions and interviewed patrons with various backgrounds in the arts. The goal was to find out these patron’s interest priorities; in other words, which aspects of the exhibit were of most interest to them as an observer. Previous literature on visitor behavior and social response at contemporary art exhibitions has been used as a base for this research. This study aims to highlight the different interest priorities as a visitor behaviour and audiens reception due to exhibition. I My respondences in this research is the exhibition visitors who had a background in art, but not necessarily in the discipline being exhibited. The results of this study will serve to determine the interest of art exhibition patrons, so that artists and curators can be made more aware of the gaps that exist between exhibit creation and viewer interest, and how those gaps can be better closed.